2009
DOI: 10.3109/09638280903204690
|View full text |Cite
|
Sign up to set email alerts
|

A population-based study of demographical variables and ability to perform activities of daily living in adults with osteogenesis imperfecta

Abstract: Adults with OI are well educated compared with the general population, and most of them are employed. High scores when tested for ADL indicate that most of them are able to live their lives independently, even though there are some differences according to the severity of the disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 28 publications
5
20
1
Order By: Relevance
“…The present study was part of a larger study describing an adult population with OI in Norway, aged 25 years and older [26]. This age limit was chosen as it is anticipated that the peak bone mass has been obtained at 25 years of age in persons with a normal skeleton [27].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study was part of a larger study describing an adult population with OI in Norway, aged 25 years and older [26]. This age limit was chosen as it is anticipated that the peak bone mass has been obtained at 25 years of age in persons with a normal skeleton [27].…”
Section: Methodsmentioning
confidence: 99%
“…On a voluntary basis, TRS has registered 259 persons with OI, but there are however no studies of the completeness of this registry. The type of OI was classified using the Sillence criteria [2], and 95 patients who fulfilled the criteria of OI type I (75 persons), type III (9 persons) or type IV (11 persons) were included [26]. Two persons were unclassified and are not included in all analyses.…”
Section: Methodsmentioning
confidence: 99%
“…However, bisphosphonates have been used successfully in the treatment of osteogenesis imperfecta in children and in young adults (Phillipi et al 2008), resulting in a 14–31% decrease in the rate of fracture, an increase in height, reduced bone pain, and better quality of life (Adami et al 2003, Sakkers et al 2004, Gatti et al 2005, Letocha et al 2005, Seikaly et al 2005, DiMeglio and Peacock 2006). These observations have not been confirmed in older patients, probably due to the low prevalence of osteogenesis imperfecta in adults, which is reported to be 31 cases per 10 6 individuals (Wekre et al 2010). …”
Section: Discussionmentioning
confidence: 90%
“…Patients with a disease that increases the risk of fractures and causes varying degrees of loss of function may have lower physical activity levels than otherwise healthy controls [87], and low physical activity itself can lead to cardiovascular disease [88]. Both Jiménez et al [80] and Radunovic et al [76,77] reported elevated body mass index (BMI) in OI patients (26 kg/m 2 and 27 kg/m 2 respectively) but normal BMI in controls (25 kg/m 2 and 24 kg/m 2 respectively).…”
Section: Temporal Relationship Of the Associationmentioning
confidence: 99%